Investigating Bdellovibrio predation: novel isolates and bioinformatics studies of predatory enzymes - Yates, Joshua (2022)
Bdellovibrio are predatory bacteria that replicate within the periplasm of their Gram-negative bacterial prey. They exhibit a biphasic lifestyle existing as free-swimming cells and inter-periplasmic growing cells. There is great interest in Bdellovibrio spp. due to their potential as antibacterial therapeutics in the current era of increasing levels of antibiotic resistance. These predators are ubiquitous in nature, being found in environments from freshwater, to soil, to the GI tracts of humans.